Computer-assisted analysis of Namibian land reform policy - Okafor, Uzochukwu Godsway Ojo (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2006.